Perspectivas del Estado en el ejercicio de nuevas políticas públicas en el Perú: Una revisión panorámica de las políticas promotoras del crecimiento económico - Pisfil Capuñay, Miguel (2006)
The purpose of this study is finding factual elements and systematizing theoretical guidelines which contribute to the understanding of the circumstantial relationship between the State –with its institutions– and civil society as well as shedding light on the total separation existing between these two groups in social and political contexts. Particularly we have tried to systematize the principal public policies which have a close relationship with economic growth identify which work efficiently or not in allocating public resources report on some Latin-American experiences on the successful implementation of public policies and outline new policies for our country which aim at promoting an articulated social approach for the structuring of a national strategy for productive development. Given its high impact in both social and economic fronts these new policies shall become pivots for the traditional policies (sectorial and social).